2019
DOI: 10.1186/s40550-019-0078-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbial quality of poultry meat in an ISO 22000:2005 certified poultry processing plant of Kathmandu valley

Abstract: Poultry meat can be contaminated by different types of microorganisms during processing in processing plant. The microbiological quality of chicken carcasses and along with processing steps and environmental condition was analyzed in this study in an ISO 22000:2005 certified poultry processing plant of Kathmandu. Standard plate count method was applied for the enumeration and detection of total mesophilic bacteria, total coliform, total faecal coliform, Staphylococcus load along with selected pathogens like Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 38 publications
2
21
0
1
Order By: Relevance
“…Staphylococci spp. of >4log10cfu/g were reported in agreement with previous studies [35,36] but higher than 1.99 log10cfu/g reported in market meat elsewhere [37].…”
Section: Microbiological Qualitysupporting
confidence: 93%
See 1 more Smart Citation
“…Staphylococci spp. of >4log10cfu/g were reported in agreement with previous studies [35,36] but higher than 1.99 log10cfu/g reported in market meat elsewhere [37].…”
Section: Microbiological Qualitysupporting
confidence: 93%
“…We suspect that the differences in bacteria counts for chicken meats in this study and previous studies might be linked to technologies used, hygienic conditions during slaughtering, processing, packaging, storage and distribution [37][38][39][40]. A study using ISO 22000:2005 certified poultry processing plant reported remarkable reductions in bacteria counts in the four sequential processing steps [37,39].…”
Section: Microbiological Qualitymentioning
confidence: 79%
“…The presence of E. coli (faecal indicator organism) in the beef indicates direct or indirect faecal contamination and this suggests a general lack of cleanliness in handling and improper storage (Centre for Food safety, 2014). Research indicates that microbial contamination occurs at every phase of processing but can be reduced through use of proper sanitation equipment and personal hygiene (Maharjan et al, 2019). Results indicated high prevalence of S. aureus in the carcass and relates to several studies that documented prevalence of S. aureus in many raw retail meats; an indication that consumers are at potential risk of S. aureus colonization and subsequent infection.…”
Section: Microbiological Contamination Of Carcass Samples Limitsmentioning
confidence: 75%
“…The counts reported in this study were higher than those reported by Briehta-Harhay et al [38] who worked with chicken meat from the United States. However, Vaidya et al [39], Lindblad et al [40], and Maharjan et al [41] in their various studies did not detect Salmonella in the chicken meat samples that were examined. Overall, the prevalence of the chilled raw chicken meat contaminated with Salmonella was estimated at 0.17 (40/240).…”
Section: Prevalence and Counts Of Salmonella In The Raw Chicken Meatmentioning
confidence: 93%
“…This value of prevalence exceeded the limits (≤ 0.1) set by the Meat Industry Guide, United Kingdom [42]. Improper handling by workers and poor hygienic conditions of the meat processing plants, as well as the meat retailing environment, are the probable sources of contamination of chicken meat sold in the open markets [41]. Improper slaughtering and manual evisceration process of the raw chicken meat intestinal contents could also be an important source of contamination of the meat with Salmonella species.…”
Section: Prevalence and Counts Of Salmonella In The Raw Chicken Meatmentioning
confidence: 99%